Value chain in agroecological organizations: analysis from the triple bottom line (2024)
The objective is to analyze organic farming as part of the bioeconomy, with emphasis on the triple base. The methodology is qualitative, using Participatory Action Research with agroecological producer communities in Tenjo and Tibacuy, Cundinamarca. In the economic dimension, it was found that producers use strategies such as barter, short circuits and the production of their own inputs. However, the lack of cost tracking and the absence of a consolidated brand are identified weaknesses. In the environmental dimension, the production of biological inputs and sustainable practices stands out, although the use of non-sustainable packaging is noted as a weakness. The lack of monitoring of the ecological footprint is identified as an aspect to be improved. In the social dimension, agroecology strengthens the community through barter, peasant markets and employment generation. However, lack of certification, limited participation in networks and low generational relay represent social challenges.